Marketing of cutflowers in Iloilo City - Celle, Nerissa M. (1995.)
This study analyzed the marketing system of cutflowers in Iloilo City. Twenty seven cutflower producers, ten producer-florists, two florist, six wholesaler-retailers and five retailers were interviewed. Cutflower varieties considered are roses, dendrobiums, vandas, anthuriums and heliconia., Rose producers marketed their produce to wholesaler-retailers, retailers, producer-florist and end users. Roses from Cebu were absorbed by wholesaler-retailers who sold the volume handled to end consumers and institutional buyer. Volume purchased by retailers were concumed by end users and florist. Dendrobiums were purchased by producer-florists and florists and passed this end consumers who also bought dendrobiums directly from producers. Vandas were either sold directly to end users or coursed through producer-florists before reaching eventual users. Anthuriums were likewise channeled either through producer-florists or florists before reaching end concumers. Heliconias on the other hand were transported to Roxas City. Cutflower producers performed harvesting, sorting and grading, defoliation and dethorning, bunching/typing, conditioning and packcaging to facilitate handling and preserve quality of flowers. Except harvesting, traders also performed the above mentioned marketing functions. Added to these however are, flower arrangement, and transportation. Cutflower producers and traders entailed an average marketing costs of P3.64 and P49.39 per dozen, respectively. Producers received an average farmgate price of P36.18 per dozen and realized a net farm price of cutflowers was P31.53 per dozen and average selling price was P103.84 per dozen. Marketing margins realized was P72.31 per dozen while net returns earned was P22.92 per dozen. Marketing problems cited by cutflower producers include low supply, spoilage, perishability, irregular buyers, consumer's lack of information on sources of cutflowers, competition, and uncollected payments. Traders on the other hand were constrained mainly by unstable supply of cutflowers, spoilage, and perishable nature of cutflowers. Low price, high market fees and food expenses, lack of sources of capital, competition, and uncollectibles were also identified as marketing problems by traders.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Cutflowers